Astigmatismo mixto paciente de sexo femenino de 58 años de edad - Moreira Vinueza, Milena Julissa (2021)
The present case study is about a 58-year-old female patient, who suffers from congenital ametropia. Reason why it is important to correct the optical defects that you present in order to preserve your visual health. In order to make an accurate diagnosis, various tests and examinations were performed, such as retinoscopy, Donders' test, biomicroscopy, Bruckner reflex, and analysis of the patient's data. The patient presented discomfort such as headache, red eye symptoms, loss of visual acuity, when analyzing the results, congenital astigmatism was determined. This has caused an increase in prescription because the patient does not like the use of the glasses.